Active learning approach for Engineering Mathematics 3 course to encourage student's motivation - Ismail, Norhafizah; Wan Ali, Wan Zah; Md. Yunus, Aida Suraya; Mohd Ayub, Ahmad Fauzi (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The process of encouraging of learning needs support from an educational environment. Engineering Mathematics is a compulsory course and an essential requirement for civil engineering students in polytechnic. In order to achieve content mastery, an active learning approach needs to be applied. Features such as role-playing, mastery learning, case studies, cooperative learning and problem solving exercises are vital. The main aim of this paper is to determine students’ acceptance of active learning, relationship between role playing and students’ motivation, and to identify the most challenging chapter in the Engineering Mathematics 3 (BA301) course. The Pearson correlation of two variables is used to analyse 80 respondents’ questionnaires. It comprises the two groups (DKA 3B and DKA 3C) of the third semester (June 2012) students of Civil Engineering at a polytechnic in Merlimau, Melaka. The sample selection is based on the engineering students enrolling in the Engineering Mathematics 3. The findings indicate the existence of a significant relationship between role playing and students’ motivation with correlation, r=0.6159. The most challenging chapter was related to the Numerical Method. It shows that while learning a challenging chapter, the facilitators or instructors need to apply active learning strategies to support the effectiveness of teaching and learning process. Hence, the motivational spirit apparently should be encouraged.